A Critical Review on the National Energy Efficiency Action Plan of Egypt - Elrefaei, Hatem; Khalifa, Marwa A. (JNRD - Journal of Natural Resources and Development, 2014)
Egypt, as with other developing countries, faces a major energy security problem, which strongly impacts all national plans for economic development. A sound energy strategy is crucially needed, and should be based on two pillars: first, boosting the production of clean energy from various renewable and non-renewable sources, and second, managing and rationalizing energy demand, with related reforms. Some steps were taken by previous Egyptian governments regarding these two pillars. In February 2008, the Ministry of Electricity and Energy of Egypt put a target of 20% of electricity to come from renewable energy resources by 2020. In July 2012, the Ministerial Cabinet approved both the Egyptian Solar Plan targeting 3500 MW of solar energy by 2027, and the National Energy Efficiency Action Plan (NEEAP) to reduce energy consumption 5% during the period from 2012-2015 compared to the average consumption of the previous 5 years. We believe that these plans will not bring their expected fruits unless they are well orchestrated with other sectoral development plans in areas such as agriculture, transport, housing and services, amongst others. This paper aims to investigate the Egyptian NEEAP and assess whether the adopted national energy efficiency plan and the associated policies on all other development sectors adopted by the government have sound implications. We aim to find out whether the development policies with a focus on energy policy are set in an integrated or fragmented way.